Interaction between pH-shifted ovalbumin and insoluble neohesperidin: Experimental and binding mechanism studies. (1st October 2022) - Xia, Na; Wang, Chunqing; Zhu, Siming
Graphical abstract: Highlights: Binding mechanisms of NH to pH-shifted OVA were investigated. The van der Waals interactions and hydrophobic interactions are involved in binding between OVA and NH. The binding affected the secondary structures of pH-shifted OVA. The NH has a high affinity for the reaction with OVA. Antioxidant activity was improved for complex compared to the pure NH. Abstract: In this study, ovalbumin (OVA) formed a complex with neohesperidin (NH) via a pH-shifting method. The NH-OVA complex self-assembled into NH-OVA nano-particles, which were then characterized and whose binding mechanism was evaluated by using multi-spectroscopic, thermodynamics, and molecular docking simulation methods. Fluorescence intensity decreased after OVA was complexed with NH. The binding constant of the OVA-NH complex was in the order of 6.32 × 10 5 M −1 suggesting that the complex is stable. Circular dichroism (CD) analysis showed that α -helix content increased, β-folding, β -turning, and irregular crimp content decreased after OVA and NH binding. Isothermal titration calorimetry results showed that hydrophobic interactions and hydrogen bonds made an important impact in the complex formation. The molecular docking results revealed that Van der Waals forces and hydrogen bonds contributed to the free binding energy of the complex. There were multiple possible surface binding sites between OVA with NH. The obtained results provide new insights into the interaction mechanism of OVA and NH, and as a vehicle for NH, the OVA has shown promising applications in functional foods.